Building The Capacity of Financial Literacy of MSMES in Bandung City to Improve Competitiveness in The International Market - Hertina, Dede; Hendayana, Yana; Ichsani, Sakina; Fatihat, Gita Genia; Pratiwi, Leni Nur (Jurnal Pengabdian UNDIKMA, 2025)
This community service program aims to enhance the financial literacy of MSMEs in Bandung City, thereby improving their competitiveness in the international market. In collaboration with KADIN Bandung City, the Faculty of Economics and Business at Widyatama University conducted a participatory training session for 15 MSME participants from the culinary, fashion, trade, and service sectors. The training combined presentations, discussions, and hands-on simulations using the SIAPIK financial application, where participants practiced recording real transactions, managing cash flow, and generating financial reports using their own business data. Post-training evaluations indicated increased digital readiness and a better understanding of financial documentation, with over 80% of participants able to independently use the SIAPIK application to produce basic financial reports. Participants also recognized the relevance of digital financial tools for accessing credit and enhancing business transparency. This program offers a scalable model for financial literacy development among MSMEs and underscores the importance of institutional collaboration for sustainability and broader adoption.